“Monster in the Classroom”: a survey study on students’ aptitude in asking question during classroom interaction in University Malaysia Kelantan, Malaysia - Yohan Kurniawan; Thana Abdullah; Khuzaiton Zakaria; Wan Mohamad Wan Abdullah (2012)
Asking question is a way to express a sense of curiosity. Curiosity is an impulse or an effective stimulus to learn and seek answers (Suhito, 1987; dalam Ribowo, 2006). Classroom teaching with lots of activities is a sign that the learning and teaching in the class exists. Communication in the classroom is very important in the learning process in a school. It relates with students’ ability to ask and communicate in the classroom. The students’ culture in Asia is very different with European or America students’ culture. Western students have the tendency to be more daring to talk in the classroom than Asian students. A research that was related to the method in the process of learning showed that the higher score was on listening and writing based on teacher’s explanation (67.56%), however the score for active speaking was very low (8.10%). At the moment, the weakness in asking questions among students in lecture rooms is due to the habit which has been brought by students since elementary until high school. This paper focuses on why students feel afraid to ask questions in lecture room? This study is a research survey to find out factors that contribute to students’ inability to ask questions in lecture room. The respondents are 200 students in Universiti Malaysia Kelantan, Malaysia from various faculties. The data collecting technique uses questionnaire which was created by the researcher himself (reliability score is 0.846). The questionnaire consists of 2 parts: Part A is internal factors and Part B is external factors. The data is analyse using SPSS as descriptive and correlation analysis. From the results we can summarise that the students are aware of the importance of asking questions in lecture room but they feel shy (majority) although lecturers encourage them to ask during the lecture. Undeniable, they want to ask but they do not know what to be asked, and they are apprehensive if their friends think that they are trying to show off. The positive side of this research indicates that the students are fully conscious that if they often ask in the lecture room, that will assist them in passing the subject easily. The students are also aware that they will easily get a position in the university’s club/ society if they are active in asking questions during their lecture hours (popularity). The other finding is the students tend to ask questions in the lecture room when the lecture topic is very interesting and prompted them to ask for a better understanding and finally, the parents’ role in encouraging them to ask questions help these students to become active in posing questions during classroom lectures.